Return of the Solow Paradox? IT, Productivity, and Employment in US Manufacturing - Acemoglu, Daron; Autor, David; Dorn, David; Hanson, Gordon H.; Price, Brendan (American Economic Review, 2014)
An increasingly influential 'technological-discontinuity' paradigm suggests that IT-induced technological changes are rapidly raising productivity while making workers redundant. This paper explores the evidence for this view among the IT-using US manufacturing industries. There is some limited support for more rapid productivity growth in IT-intensive industries depending on the exact measures, though not since the late 1990s. Most challenging to this paradigm, and to our expectations, is that output contracts in IT-intensive industries relative to the rest of manufacturing. Productivity increases, when detectable, result from the even faster declines in employment.